British-Irish historical memory: the legacy of the Anglo-Irish conflict in the first four volumes of the Lives Entwined project - Slimane Hargas (Revue LISA)
The very name given to the project initiated by the British Council in the mid-2000s, i.e. Lives Entwined, set the tone for the four volumes of essays it has hitherto given birth to, and in which the overarching themes are indeed the strong cultural and historical ties linking British and Irish people and the main stumbling blocks to their reconciliation in decades past, namely the exacerbation of the memory of their strife-ridden past by British imperialism and Irish nationalism, as well as the Troubles in Northern Ireland. This article shall attempt to determine the extent to which the personal accounts given by the contributors to Lives Entwined testify to the “postcolonial recalibration” of British-Irish relations referred to by Tony Reilly in his introductory remarks to the first volume. It shall be argued that while Reilly’s statement is not wide of the mark, the overwhelming majority of the contributors highlighting the end of an era fraught with historical tension between Britain and Ireland, and the emergence, in its stead, of a new and more peaceful one, this assessment of the situation should not be taken for granted too easily nowadays, given the political turmoil brought about by Brexit.